Literary and Analytical Study of the Source Plants of Kshara (Alkali) for Ksharasutra Preparation in the Management of Fistula-in-ano - G.V.P. Samaranayake; W.A.L.C. Walivita; K.M. Chandimal (Biogenesis: Jurnal Ilmiah Biologi, 2020)
The different surgical techniques and importance in disease treatment were explored by Sushruta, the father of surgery. Furthermore, Anushastra or parasurgical substances and methods from Ayurveda are distinctive in surgical fields as discovered by Sushruta. Kshara or alkali are useful for performing excision/removal, incision/cutting, scraping, alleviating three Doshas and several special procedures, and therefore superior to Shastra (sharp instruments) or Anu Shastra (accessory apparatuses). Also, Kshara is derived from diverse Ayurveda plants and applied in different ways to manage various diseases, including bhagandara (fistula-in-ano) and other numerous anorectal conditions. This study implemented a literary analysis of the plant sources employed to prepare Kshara sutra. There are 23 Kshara source plants provided by Sushruta. The specimens were identified by a comparison of the description to previously published Kshara sutra references. The data recorded encompassed botanical name, local label, location, pharmacodynamics, morphology characteristics, action, chemical constituents, and antimicrobial activity. There are three source plants provided by Sushruta to prepare Kshara sutra for fistula-in-ano management in this study including Curcuma longa Linn., Commiphora mukul, and Euphorbia antiquorum. It is possible to become a reference for Kshara sutra, a novel drug delivery system in Ayurvedic surgery for anorectal diseases and involves a thread smeared with kshara (alkali) applied to induce both mechanical and chemical cutting and healing.